Fiscal policies and credit regimes: A TVAR approach - Tommaso Ferraresi; Andrea Roventini; Giorgio Fagiolo (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2013)
In the present work we investigate how the state of credit markets non-linearly affects the impact of fiscal policies. We estimate a Threshold Vector Autoregression (TVAR) model on U.S quarterly data for the period 1984-2010. We employ the spread between BAA-rated corporate bond yield and 10-year treasury constant maturity rate as a proxy for credit conditions. We find that the response of output to fiscal policy shocks are stronger and more persistent when the economy is in the tight credit regime. The fiscal multipliers are abundantly and persistently higher than one when firms face increasing financing costs, whereas they are feebler and often lower than one in the normal credit regime. On the normative side, our results suggest policy makers to carefully plan fiscal policy measures according to the state of credit markets.
Keywords: J32; E32; E44; E62; 330; fiscal policy; threshold vector autoregression (TVAR); non-linear models; impulse-response functions; fiscal multipliers; credit frictions; financial accelerator